2014
DOI: 10.4236/wjcmp.2014.42013
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Coefficient in Silicon Solar Cell with Applied Magnetic Field and under Frequency: Electric Equivalent Circuits

Abstract: In this paper, a theory on the determination of the diffusion coefficient of excess minority carriers in the base of a silicon solar cell is presented. The diffusion coefficient expression has been established and is related to both frequency modulation and applied magnetic field; the study is then carried out using the impedance spectroscopy method and Bode diagrams. From the diffusion coefficient, we deduced the diffusion length and the minority carriers' mobility. Electric parameters were derived from the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
(7 reference statements)
0
23
0
Order By: Relevance
“…Capacitance study: Diffusing capacitance of the solar cell is considered as the ability of the resulting charge variation during the process of diffusion within the solar cell (Sane et al, 2013;Hamidou et al, 2013;Diao et al, 2014;Barro et al, 2015). It is given by the following equation:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Capacitance study: Diffusing capacitance of the solar cell is considered as the ability of the resulting charge variation during the process of diffusion within the solar cell (Sane et al, 2013;Hamidou et al, 2013;Diao et al, 2014;Barro et al, 2015). It is given by the following equation:…”
Section: Resultsmentioning
confidence: 99%
“…Sf and Sb are respectively the junction and back surface recombination velocity (Sane et al, 2013;Hamidou et al, 2013;Diao et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the position of the solar cell and the emitting source of the magnetic field, one can note some effects on the solar cells devices. That is why some works concerning influence of magnetic field on solar cells are done [12] [19] [20]. It is shown that, the peak power (P m ), the short-circuit photocurrent, the photo voltage and the solar cell diffusion capacitance which is reduced to the Shockley's depletion model decrease with the magnetic field when the solar cells is operating in steady state [21].…”
mentioning
confidence: 99%
“…It is shown that, the peak power (P m ), the short-circuit photocurrent, the photo voltage and the solar cell diffusion capacitance which is reduced to the Shockley's depletion model decrease with the magnetic field when the solar cells is operating in steady state [21]. It has been also proved that under frequency modulation, the electron intrinsic mobility (µ), the diffusion coefficient (D), and the diffusion length (L) decrease when the silicon solar cell is both under applied magnetic field and frequency illumination mode [12].…”
mentioning
confidence: 99%
“…In frequency dynamic regime [8] [9], the well known impedance spectroscopy method is used for the determination of electrical parameters. For this work, we use Bode and Nyquist diagrams [10] [11] to show the effect of the wavelength and the junction recombination velocity on the diffusion capacitance of a vertical parallel junction silicon solar cell characterized by the lateral collection.…”
Section: Introductionmentioning
confidence: 99%